Perancangan model simulasi untuk meningkatkan jumlah penumpang Bus Transjakarta menggunakan soft system methodology dan Agent Based Model - Iphov Kumala Sriwana; M. Agung Saryatmo; Erwin Saputra (Universitas Mercu Buana, 2019)
Jakarta is one of the cities in Indonesia with public transport services that have not been optimal. The quality index of public transport in Jakarta is only 18%, far lower than the average quality index of public transport in Indonesia which reaches 38.67%. Until 2016, the number of public transport users in Jakarta was only 24%, while ideally the number of public transport users was 60%. This shows the low interest of the people of Jakarta to use public transportation. One of the public transportation is Transjakarta Bus, where since 2011, the number of Transjakarta Bus passengers tends to be stagnant. This study aims to identify the actual problems experienced by Transjakarta Corridor Bus passengers using Soft Systems Methodology and then simulate using Agent Based Models. The use of Soft Systems Methodology produces nine model activities that can be carried out by PT. Jakarta Transportation to improve the Corridor 8 Transjakarta Bus system, so as to increase the number of passengers. The use of simulations with an agent based model shows that increasing speed and BRT scores can increase the number of passengers, but the increase in the number of passengers on the Transjakarta Bus will be more optimal if supported by a reduction in headway and the percentage of single buses. Increased passengers can occur as much as 6.83 to 44.38%.